Analisis Spasial Cakupan Imunisasi di Kabupaten Serang, Indonesia di Tahun 2021 - Fitri, Laelatul; Makful, Martya Rahmaniati (Universitas Faletehan, 2024)
The incidence of deaths of children under five years of age in low- and middle-income countries due to imperfect immune system was estimated to increase, which actually can be prevented and reduced by immunization. In 2021, Banten Province received the highest immunization rating in Indonesia with coverage of 94.8%. However, in its Serang Regency, complete basic immunization coverage was only 89.2%. The aim of this study was to find out the spatial distribution of complete immunization coverage in Serang Regency, Banten Province, Indonesia in 2021. This research used an ecological study design with spatial analysis to estimate and analyze the distribution of immunization coverage in 29 districts in Serang Regency by looking at the number of integrated health post (Ina. posyandu) and the number of midwives spread across them. The analysis results showed a negative spatial autocorrelation of immunization coverage in Serang Regency in 2021. There was 1 district included in quadrant II (low-high), namely Bandung District and 1 district included in quadrant IV (high-low), namely Padarincang District.